Herencia de la resistencia al daño mecánico causado por Tagosodes orizicolus (Muir) (Homoptera-Delphacidae) en arroz Oryza sativa - Cuevas P. Federico; Pardey R. Catherine; Baena García Diosdado (Acta Agronómica)
In Colombia all rice varieties developed are reported as resistant to Tagosodes orizicolus. Given the narrow genetic base of the resistant sources, this study was undertaken to identify the resistant parents or donors more oftenly used in Latin America. The materials were characterized as resistant (Mudgo, Amistad 82, IRAT 120, IRAT 124, Makalioka) or susceptible based on the free chosen test and non chosen test and on the survival and oviposition of the insect (Chianan 8, Colombia 1, Bluebonnet 50, IR 8 (lCA), IR 8 (IRRI), Tetep and Cica 8). The damage was associated with insect survival, oviposition and eggs eclotion. To determine heritability two parents (Makalioka and Mudgo), were crossed with IR 8 F1 and F3 populations were also evaluated based on the free chosen test. En Colombia las variedades de arroz desarrolladas se consideran como resistentes a Tagosodes orizicolus. Dada la estrechez genética de las fuentes de resistencia, se inició este estudio para identificar los progenitores donantes de resistencia usados con mayor frecuencia en América Latina. Los materiales se caracterizaron como resistentes (Mudgo, Amistad 82, IRAT, 120, IRAT 124 Y Makalioka) o susceptibles (Chianan 8, Colombia 1, Bluebonnet 50, IR 8 (lCA), IR (IRRI), Tetep y Cica 8), con base en las pruebas de libre escogencia, no escogencia, sobre vivencia y oviposición. El daño estuvo asociado con la supervivencia, oviposición y eclosión de huevos del insecto. Para la determinación de la herencia se cruzaron los progenitores Makalioka y Mudgo con IR8. En la Progenie F1 del cruzamiento resistente x resistente el 111% de las plantas fueron susceptibles; Mudgo y Makalioka segregaron 23 y 41% de plantas susceptibles.